Learning to fear: predator recognition in giraffes is shaped by evolved sensitivity and ecological experience - Baotic, Anton; Szipl, Georgine (Frontiers in Ecology and Evolution, 2025)
IntroductionPredator recognition is essential for prey survival, yet, whether responses are shaped by evolutionary predispositions or by ecological experience remains debated.MethodsWe tested vigilance responses of fifty-one free-ranging Southern giraffes (Giraffa giraffa) to controlled playbacks of lion roar-grunt sequences in two South African populations: a predator-naïve population in a reserve without lions and a predator-experienced population in a reserve where lions were reintroduced five years ago.ResultsBoth populations oriented rapidly to lion calls, suggesting that acoustic features of lion vocalizations act as generalized danger cues. However, predator-experienced giraffes sustained vigilance ten times longer (mean ± SD: 513.34 ± 421.34 s, N = 24) compared to predator-naïve giraffes (49.06 ± 46.26 s, N = 27). Vigilance responses during lion playbacks, in general, were higher in the predator-experienced population, whereas responses to control calls did not differ between sites.DiscussionThese findings indicate that while immediate orientation likely reflects evolved sensitivity to acoustically harsh predator cues, the persistence of vigilance is shaped by ecological experience. Our study demonstrates that predator reintroduction can rapidly recalibrate prey risk perception, highlighting the dynamic interplay between evolved predispositions and learning in shaping antipredator responses.